Improving the Preparation and Prescription of a Homeopathic Remedy - Dicke, Martin (Homœopathic Links, 2018)
In this short article, a simple test is suggested for the control and standardisation of the dynamisation process in homeopathy. Furthermore, the habit of direct administration of homeopathic remedies is mentioned and a more professional way of prescribing is shown.
Keywords: Succussing; Dynamisation; Electronic prescription system; Unique identifying number